Mechanical Properties of Boron-Treated Ferritic GGG40.3 Ductile Cast Iron - Unal, Fatma; Topuz, Ahmet (CARL HANSER VERLAG, 2014)
In this paper, some properties of borided ferritic GGG40.3 ductile iron samples were investigated. Box-boronizing was carried out at 850 degrees C and 950 degrees C for 1 h, 2 h, and 4 h with Ekabor I powder. After the experiments, the formed FeB and Fe2B phases in the ductile irons were confirmed by X-ray diffraction analysis. The tooth-shaped morphology of the boride layers was examined by optical microscopy. Fracture toughness and the hardness of boride layer were measured by Vickers method. Abrasive tests were done using ball-on-disc test apparatus. An aluminum oxide (Al2O3) ball was used in the abrasion experiments and the samples were subjected to abrasion under a load of 30 N at a constant sliding speed. It was determined that the thickness of boride layers obtained by using Ekabor I powder ranged from 38 mu m to 198 mu m, and the hardness of boride layers ranged between 1173 HV and 1820 HV. The fracture toughness values ranged from 2.79-3.78 MPa m(1/2).
Keywords: Materials testing; box-boronizing; ductile iron; mechanical properties; Materials Science